ANALISIS PERHITUNGAN, PEMOTONGAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 23 ATAS JASA ANGKUT: STUDI KASUS PADA PUSKUD RIAU - Niken Nindika Sundayu; Dian Puji Puspita Sari (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study analyzes the calculation, withholding, and reporting of Income Tax (PPh) Article 23 on transportation services at PUSKUD Riau, assessing the company’s compliance with prevailing tax regulations. Using a qualitative descriptive approach and secondary data from 2023–2024 transaction records, the results show that PUSKUD Riau generally applied the correct 2% PPh Article 23 rate. However, double-calculation errors caused overstatements in two transactions, and documentation was incomplete in some periods. Although most filings were timely, weaknesses in the administrative and documentation systems could lead to administrative penalties. The study recommends implementing a more systematic documentation process and adopting tax software to enhance the accuracy of PPh Article 23 calculations and reporting.